MOOCs and Trello Based Blended Learning to Increase Student Involvement - Connie Connie; Eko Risdianto (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to see student responses to learning with blended learning based on MOOCs and Trello. This type of research is quantitative research with a survey method. The instrument used is a closed questionnaire using a modified Likert scale with 4 answer options, namely strongly agree with a score of 4, agree with a score of 3, disagree with a score of 2, and strongly disagree with a score of 1. The questionnaire used consists of 29 statement items about the response after using the Trello project management application. Data processing is done using the help of an excel application. The results obtained as a whole are either from a limited test or from the results of an extensive test. The Trello application in learning has a positive response from the respondents.There are no items that agree to disagree or strongly agree based on the respondent's data, but all items agree.